HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA SISWA SMPN DI PEKANBARU - Atika Maulida Sari; Yanti Ernalia; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTThe prevalence of obesity in Riau Province among early adolescence class above the national average figure based on data from Health Research (RISKESDAS) 2013. It is a serious problem. Physical activity is the most dominant factor for increasing the obesity. Regular activity can regulate body weight and prevent various diseases. This research was an observational analytical. This research was conducted with the cross-sectional design in which samples were selected with a cluster sampling method. Physical activity was obtained through a questionnaire of physical activity and the incidence of obesity was assessed by measuring BMI. Based on this study of 279 samples were obtained 68.8% of the respondents were female, as many as 55.9% of respondents had obese, and 52% of respondents mild physical activity. From the results of the analysis carried out there was no significant relationship among physical activity with obesity (p = 0.480). So, there was no significant relationship among physical activity with obesity at junior high school student’s in Pekanbaru (p> 0.05).Keywords: Physical activity, obesity, Junior High School Student’s